Search for a W ' boson decaying to a muon and a neutrino in pp collisions at root s=7 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; Ghete, V; et al. (2011)
A new heavy gauge boson, W', decaying to a muon and a neutrino, is searched for in pp collisions at a centre-of-mass energy of 7 TeV. The data, collected with the CMS detector at the LHC, correspond to an integrated luminosity of 36 pb-1. No significant excess of events above the standard model expectation is found in the transverse mass distribution of the muon-neutrino system. Masses below 1.40 TeV are excluded at the 95% confidence level for a sequential standard-model-like W'. The W' mass lower limit increases to 1.58 TeV when the present analysis is combined with the CMS result for the electron channel. © 2011 CERN.